The Survey of Nursing Students’ Dependence on Using Google Translate in English Class - Santa Maya Pramusita (ETERNAL (English Teaching Journal), 2023)
Google Translate (GT) is without a doubt well-liked among students learning English in an EFL context due to the numerous conveniences it provides. Recently, a unique phenomenon was found among nursing students of Pelita Harapan University where they appeared to rely on GT in order to complete English assignments. To figure out how reliant these students toward GT and the reasons behind it, this study was conducted. The method utilized was mixed-method sequential explanatory design, with questionnaire and semi-structured interview serving as instruments. While the respondents of this study encompassed 176 second-year nursing students. The results showed that 35 students (20%) were in the highly dependent category, 47 students (27%) were in dependent category, 66 students (37%) were in independent category, and 28 students (16%) were in independent category. Further research examining the impact of GT on nursing students’ English achievement is needed to better understand the phenomenon.